Uso da informação contábil-financeira para tomada de decisão: o caso de uma empresa comercial - Valtemar de Andrade Braga (2001)
Study on the use of financial-accounting information for decisionmakingin a retail company. It investigates the managerial style prevailing in thatfirm, elaborates on the role of managers as information users, evaluates the role of information for management and for investment strategies. In addition it focuses on the influence of internal and external factors in decision-making process, and the financial-accounting information engendered and utilized in the investigated firm. It also analyses the quality and importance of information, as well as how it is collected, distributed and utilized within the organization. The study also emphasizes the importance of accounting information for the decision making process.